Metodologias interativas para facilitar a integração da Unidade Curricular de Semiologia Humana (Interactive Methodologies to facilitate the integration of Human Semiology Curriculum Unit) - Andrade, Maria Cristina de; Mangia, Cristina; Barragán, Elena; Diniz, Roseani; Strufaldi, Maria Wany Lousada; Mennin, Regina Helena Petroni (Revista Eletrônica de Educação, 2019)
Introduction: Curriculum integration is critical to medical education. It represents a constant challenge for teachers since there is no shared concept about what it means, what is to be included, and the dynamics of operationalization. Objectives: To promote and implement the integration of a human semiology curriculum module (medical clinic, pediatrics, diagnostic imaging, psychology and health informatics) through interactive methodologies; to evaluate the students perception of the module. Methods: Action research involved 76 teachers and 125 third-year medical students. Monthly meetings were held between the coordinators. Discussions focused on monitoring and following-up on implementation of interactive methodologies and reviewing integration of theory and practice. Also included were the implementation of a joint discussion of clinical cases, a holistic view of the patient and presenting problems. Collaboration and communication between teachers, joint classes, integrated evaluation of the process of learning and teaching in small groups. In addition, training workshops were held for the use of a Moodle platform by teachers for page construction of Curriculum Module. The evaluation of students' perceptions was performed through a voluntary and anonymous questionnaire with open questions (qualitative). All 125 students answered the questionnaire. A five-point Likert scale was used with a midpoint indicating intermediate or nullity, domain of discordance (values 1 and 2) and domain of cordance (4 and 5). The analysis of the data was made comparing their results with those obtained in the tests of the previous year. The Statistical Package for the Social Sciences (version 17.0, SPSS®, Chicago, IL, USA). Results: Data analysis showed that there was a positive impact after the integration between the subjects and the introduction of interactive methodologies in the course. Give the data for this statement here. There was a significant improvement in performance, both theoretical and practical, as measured by the scores obtained by the students, when compared to the students of the previous year (p <0.001). On the other hand, in open questions, students still mentioned heterogeneity among teachers and in the evaluation. They students also commented on, the need for a continuous effort to improve and maintain the integration and adjust their workload. Conclusion: The evaluation analysis supported the need to continue to implement teacher development, joint planning and the continuity of the articulation process. The integration of interactive methodologies was shown to improve student performance compared to the previous class in a Semiology Curricular Module. Resumo Introdução: A integração do currículo é fundamental para a formação médica. Representa, todavia, um constante desafio para os professores envolvidos, visto que não há uniformidade sobre o conceito, sobre a necessidade de inclusão de atividades integradas, e mesmo sobre sua operacionalização. Objetivos: Promover a integração da unidade curricular (UC) de semiologia humana (clínica médica, pediatria, diagnóstico por imagem, psicologia e informática em saúde) através da implantação de metodologias interativas, e avaliar a percepção dos estudantes do módulo de semiologia humana, após a implementação destas metodologias. Métodos: Utilizou-se pesquisa-ação, envolvendo 76 professores e 125 estudantes da 3ª série do curso médico. Para a integração da UC foram realizadas: reuniões mensais entre os coordenadores para implementação e acompanhamento das metodologias interativas, que consistiram de integração da teoria com a prática, implantação de discussão conjunta de casos clínicos, visão holística do paciente e de seus problemas, colaboração e comunicação entre os professores, aulas conjuntas, avaliação integrada com o processo de aprendizagem e ensino em pequenos grupos. Além disso, foram realizadas oficinas de capacitação para uso da plataforma Moodle pelos professores e construção de página com as atividades da UC. A avaliação da percepção dos estudantes sobre a UC foi realizada através de questionário voluntário e anônimo e de questões abertas (qualitativa). Todos os estudantes responderam ao questionário. Foi utilizada a escala de Likert de cinco pontos com um ponto médio manifestando situação intermediária ou de nulidade, domínio de discordância (valores 1 e 2) e domínio de concordância (4 e 5). A análise do desempenho destes alunos da 3ª série do curso de medicina foi feita comparando-se os seus resultados com os obtidos nas provas do ano anterior. Na análise estatística foi utilizado o Statistical Package for the Social Sciences (versão 17.0, SPSS®, Chicago, IL, EUA). Resultados: A análise conjunta das categorias do questionário demonstrou que houve impacto positivo após a integração entre as disciplinas e a introdução de metodologias interativas no curso. Houve melhora significante do desempenho, tanto teórico quanto prático, avaliado pelas notas obtidas pelos alunos, quando comparado aos alunos do ano anterior (p<0,001). Por outro lado, nas questões abertas, os alunos ainda referiram heterogeneidade entre os professores e na avaliação, necessidade de um esforço contínuo para melhorar e manter a integração, bem como adequar a carga horária, considerada insuficiente. Conclusão: A análise da avaliação evidenciou a necessidade de implementar o desenvolvimento docente, o planejamento conjunto e a continuidade do processo de articulação. A utilização das metodologias interativas contribuiu para a integração da Unidade Curricular de semiologia. Resumen Introducción: La integración del currículo es fundamental para la formación médica. Sin embargo, representa un constante desafío para los profesores involucrados, ya que no hay uniformidad sobre el concepto, sobre la necesidad de inclusión de actividades integradas, y incluso sobre su operacionalización. Objetivos: Promover la integración de la unidad curricular (UC) de semiología humana (clínica médica, pediatría, diagnóstico por imagen, psicología e informática en salud) a través de la implantación de metodologías interactivas, y evaluar la percepción de los estudiantes del módulo de semiología humana, después de la aplicación de estas metodologías. Métodos: Se utilizó investigación-acción, involucrando a 76 profesores y 125 estudiantes de la 3ª serie del curso médico. Para la integración de la UC se realizaron: reuniones mensuales entre los coordinadores para implementación y seguimiento de las metodologías interactivas, que consistieron en la integración de la teoría con la práctica, implantación de discusión conjunta de casos clínicos, visión holística del paciente y de sus problemas, colaboración y comunicación entre los profesores, clases conjuntas, evaluación integrada con el proceso de aprendizaje y enseñanza en pequeños grupos. Además se realizaron talleres de capacitación para uso de la plataforma Moodle por los profesores y construcción de página con las actividades de la UC. La evaluación de la percepción de los estudiantes sobre la UC se realizó a través de un cuestionario voluntario y anónimo y de cuestiones abiertas (cualitativa). Todos los estudiantes respondieron al cuestionario. Se utilizó la escala de Likert de cinco puntos con un punto medio manifestando situación intermedia o de nulidad, dominio de discordancia (valores 1 y 2) y dominio de concordancia (4 y 5). El análisis del desempeño de estos alumnos de la 3ª serie del curso de medicina se hizo comparando sus resultados con los obtenidos en las pruebas del año anterior. En el análisis estadístico se utilizó el Statistical Package for the Social Sciences (versión 17.0, SPSS®, Chicago, IL, EE.UU.). Resultados: El análisis conjunto de las categorías del cuestionario demostró que hubo impacto positivo tras la integración entre las disciplinas y la introducción de metodologías interactivas en el curso. Se observó una mejora significativa del rendimiento, tanto teórico como práctico, evaluado por las notas obtenidas por los alumnos, en comparación con los alumnos del año anterior (p <0,001). Por otro lado, en las cuestiones abiertas, los alumnos todavía refirieron heterogeneidad entre los profesores y en la evaluación, necesidad de un esfuerzo continuo para mejorar y mantener la integración, así como adecuar la carga horaria, considerada insuficiente. Conclusión: El análisis de la evaluación evidenció la necesidad de implementar el desarrollo docente, la planificación conjunta y la continuidad del proceso de articulación. La utilización de las metodologías interactivas contribuyó a la integración de la Unidad Curricular de semiología. Keywords: Semiology, Medical education, Student, Methodology. Palavras-chave: Semiologia, Educação médica, Estudante, Metodologia. Palabras clave: Semiología, Educación médica, Estudiante, Metodología. References ALMEIDA, Maria José de. Gestão da escola médica: crítica e autocrítica. Rev Bras Educ Med, 32 (2):202-9, março, 2008. BATALDEN, Paul; DAVIDOFF, Frank. Teaching quality improvement: the devil is in the details. JAMA, 298 (9):1059-1061, September, 2007. CARR, Wilfred; KEMMIS Stephen. Teoría crítica de la enseñanza. Barcelona: Martinez Roca, 1988, 245p. DOLL JR., William E. Currículo: uma perspectiva pós-moderna. Porto Alegre: Artes Médicas, 1997. 224p. FOGARTY Robin. Ten ways to integrate curriculum. Educ Leadersh, 49(2):61-5, October, 1991. HARDEN Ronald M.; LAIDLAW, Jennifer M. Essential skills for a medical teacher. Edinburgh: Elsevier, 2012, 272p. HARDEN, Ronald M.; SOWDEN, Susette; DUNN, William R. Some educational strategies in curriculum development: The SPICES model. Med Educ, 18 (4): 284-297, July, 1984. HARDEN, Ronald M. Change – Building windmills not walls. Medical Teacher, 20 (3): 189-191, 1998. HARDEN, Ronald M. The integration ladder: a tool for curriculum planning and evaluation. Med Educ, 34 (7): 551-557, July, 2000. HOLLANDER, Harry; LOESER, Helen; IRBY, David. An anticipartory quality improvement process for curricular reform. Acad Med, 77(9): 930, September, 2002. JANSSEN-NOORDMAN, Ameike M.B.; MERRIËNBOER, Jeroen J.G.; VAN DER VLEUTEN, Cees P.M.; SCHERPBIER Albert J.A. Design of integrated practice for professional learning competences, Medical Teacher, 28(5): 447-452, August, 2006. MALIK, Alam Sher; MALIK Rukhsana Hussain. Twelve tips for developing an integrated curriculum. Med Teach, 33 (2): 99-104, 2011. MENNIN, Stewart P.; KRACKOV, Sharon K. Reflections on relevance, resistance, and reform in medical education. Academic Medicine. 73(9): S 60-64, September, 1998. MINISTÉRIO DA EDUCAÇÃO E CULTURA. Conselho Nacional de Educação. Câmara de Educação Superior. Parecer CNE/CES de 2014. Institui as Diretrizes Curriculares Nacionais do Curso de Graduação em Medicina. Brasília (DF). Conteúdo online disponível em: http://portal. mec.gov.br/cne/arquivos/pdf/CES1133.pdf, acesso em 2006. MIRANDA, Marilia Gouvea de; RESENDE Anita C. Azevedo. Sobre a pesquisa-ação na educação e as armadilhas do praticismo - Revista Brasileira de Educação, v. 11, n. 33, set./dez, 2006. MULLER, Jessica H.; JAIN, Sharad; LOESER, Helen; IRBY, David M. Lessons learned about integrating a medical school curriculum: perceptions of students, faculty and curriculum leaders. Med Educ, 42(8), p.778-85, agosto, 2008. PERERA, Jennifer; LEE, Nagarajah; WIN, Khin; PERERA, Joachim; WIJESURIYA, Lionel. Formative feedback to students: the mismatch between faculty perceptions and student expectations, Medical Teacher, 30 (4): 395-399, 2008. PRIDEAUX, David; ASH, Julie K. Integrated learning. In: DENT, John A.; HARDEN, Ronald M. A practical guide for medical teachers. 4. ed. London: Elsevier, p.183-189, 2013. PUCCINI, Rosana Fiorini; SAMPAIO, Lucia de Oliveira; BATISTA, Nildo Alves. A Formação médica na Unifesp – excelência e compromisso social. São Paulo: Editora Unifesp, 2008, 312p. STEINERT Yvonne; MANN, Karen; CENTENO, Angel; DOLMANS, Diana; SPENCER, John; GELULA, Mark; DAVID, Prideaux. A systematic review of faculty development initiatives designed to improve teaching effectiveness in medical education: BEME Guide No. 8. Med Teach, 28(6): 497-526, September, 2006. TINTO, Vincent. Stages of student departure. Reflections on the longitudinal character of student leaving. Journal of Higher Education, 59(4): 438-455, Jul-Aug, 1998. Conteúdo online disponível em: http://www.edu.plymouth.ac.uk/resined/actionresearch/arhome.htm, acesso em 2006. WATER-ADAMS. Action research in education - Conteúdo online disponível em: http://www.edu.plymouth.ac.uk/resined/actionresearch/arhome.htm, acesso em 2006.